Characterizing the lithic raw materials from Fuente del Trucho (Asque‐Colungo, Huesca): New data about Palaeolithic human mobility in north‐east Iberia. (11th October 2020) - Sánchez de la Torre, M.; Utrilla, P.; Montes, L.; Domigo, R.; Le Bourdonnec, F.‐X.; Gratuze, B.
Abstract : Fuente del Trucho cave (Asque‐Colungo, Huesca, Spain) is located in the central Pre‐Pyrenean range in north‐east Iberia, in the Arpán ravine, a tributary of the Vero River. The mouth of the cave is 22 m wide and it is oriented to the south‐east. The entrance gives access to a 24 m‐deep hall. Palaeolithic paintings were discovered in the cave in 1978. The Fuente del Trucho art comprises two sectors: the external with some engraved motifs and the internal featuring more than 100 painted motifs distributed in 21 panels. Archaeological works have been undertaken since 1979, identifying several human occupations from the Middle and Upper Palaeolithic. This paper presents results obtained after the analysis of lithic raw materials. The analyses were performed using the classical archaeopetrological approach, which comprises textural, micropalaeontological and petrographical analyses, combined with the application of geochemical methods, using energy‐dispersive X‐ray fluorescence (ED‐XRF) and laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS). The results show that chert and quartzites were the most commonly used rocks. Different types and origins of chert were identified, demonstrating the existence of a wide mobility for lithic raw material procurement during all the Palaeolithic occupations.